Simple Kinetic-Spectrophotometric Method for the Determination of Mn(II) in Water - Kaushik, R.D.; Devi, Sumitra; P. Singh, Raghvendra; Shashi (Asian Journal of Chemistry, 2016)
A new kinetic-spectrophotometric method based on the Mn(II) catalyzed periodate oxidation of m-anisidine (MMA) in acetone-water medium has been developed for 1.0 nanogram/mL to 120.0 nanogram/mL determination of Mn(II) in water samples. Molar absorptivity (99.0099 × 103-165.0165 × 103 L mol-1 cm-1 Sandell's sensitivity (0.556-0.333 ng/cm2), correlation coefficient (0.9998-1.000) and effect of few interferrants have been worked out for developing the calibration curves in terms of absorbance or initial rate or pseudo first order rate constant vs. [Mn(II)] plot. The method is simpler, more sensitive with improved detection limits in comparison to the reported methods and especially useful in absence of the expected interferrants.